Tin‐Based Perovskite with Improved Coverage and Crystallinity through Tin‐Fluoride‐Assisted Heterogeneous Nucleation. Issue 1 (30th November 2017) - Xiao, Min; Gu, Shuai; Zhu, Pengchen; Tang, Mingyao; Zhu, Weidong; Lin, Renxing; Chen, Chuanlu; Xu, Weichao; Yu, Tao; Zhu, Jia
Abstract: Tin fluoride (SnF2 ) is widely used as an effective additive for lead‐free tin‐based perovskite solar cells. However, the function of SnF2 and the mechanism in improving the film morphology are still not clear. In this work, it is clearly demonstrated that SnF2 can play a crucial role in the crystal nucleation process. Due to the limited solubility, SnF2 creates more nucleuses for the crystal growth and therefore enables more uniform thin film with high coverage. It is confirmed that this mechanism can be applied to the growth of both thin film and single crystal. As a result of tin‐fluoride‐assisted heterogeneous nucleation, an MASnIBr2 ‐based perovskite solar cell with a high and stable power conversion efficiency of 3.70% is demonstrated. Abstract : SnF2 can serve as heterogeneous nucleation sites to facilitate crystal growth of tin‐based perovskite crystal . The addition of SnF2 with appropriate concentration can enable tin‐based perovskite film with full coverage and improved crystallinity and reduced carrier recombination. As a result, a tin‐based PSC with stable efficiency of 3.70% is demonstrated.